Study on microscopic mechanism of wetting anthracite by charged droplets - Hongjie ZHANG; Yuming ZHAO; Shaocheng GE; Weizhi ZHAO (Meikuang Anquan)
As a new type of high-efficiency dust removal method, water-mist charge-enhanced dust reduction technology has been shown to significantly improve the efficiency of coal dust management in comparison with traditional wet spray dust reduction technology. However, the microscopic mechanism of the technology on coal dust capture and wetting has not yet been thoroughly explained. In this study, a multi-scale approach was adopted to experimentally investigate the wetting performance of charged droplets and the electrostatic agglomeration of anthracite dust. Secondly, the molecular simulation method was employed to investigate the interaction mechanism between the charged droplets and anthracite from the dimensions of electronic structure calculation at the quantum mechanical level and conformational evolution at the molecular dynamics level. The findings indicate that the charged solutions exhibited superior wetting performance on coal dust, with the contact angle between charged droplets and coal dust showing an overall downward trend as the charging voltage increased, and the minimum contact angle and optimal wetting performance were achieved at −24 kV charging voltage. The particle size distribution of coal dust after charged spray sedimentation showed significant enlargement, with distribution trends shifting towards 100 μm, indicating the existence of electrostatic agglomeration of coal dust by charged droplets. Compared to ordinary water molecules, charged water molecules demonstrated enhanced polarity, presented uniformly negative electrostatic potential distributions, and exhibited greater electrostatic potential differences with anthracite molecules, suggesting stronger electrostatic interactions. Charged water molecules displayed higher adsorption density on anthracite surfaces, formed more compact molecular layers, and generated increased hydrogen bond quantities within the system. Furthermore, the energy composition analysis confirmed that electrostatic effect is the dominant factor in the interaction between charged water molecules and anthracite molecules.